SAT0602 Is A Brief Education Intervention Effective To Motivate Patients To Stop Smoking?. (15th July 2016) - Tekkatte, R.; Williamson, L.; Price, E.; Carty, S.
Abstract : Background: Smoking has been associated with an increased risk of developing rheumatoid arthritis (RA), more severe disease and poor response to disease modifying drugs (DMARD). Motivation is the most important aspect of giving up smoking and also awareness of its ill-effects, self-confidence and support. Objectives: We have looked at the immediate effect on patient motivation to stop smoking by creating awareness of its ill-effects. Methods: We surveyed Rheumatology outpatients with an anonymous questionnaire including demographics, smoking status, education status, employment status and awareness of the ill-effects of smoking. Motivation to stop smoking was assessed by 10cm Visual analogue scale (VAS) before and after receiving information on adverse effects of smoking on RA. The information provided was about increased risk of RA, severe disease and poor response to DMARD. Results: 100 unselected patients completed the questionnaire: 74% female; 46% RA; 22% current smokers; 37% never smokers; 41% ex-smokers. 68% of patients in all categories had attended secondary school. A higher proportion of never smokers had attended University compared with current smokers [20% (8/37) vs. 5% (1/22)]. A higher proportion of current smokers were unemployed as compared with never smokers [32% (7/22) vs. 8% (3/37)]. 50% of patients stated that they had never asked about smoking during consultations. When asked how important smoking is in arthritis, 55% of all patients scored >8/10 on a VAS (0=not bad /10=very bad). There was no significant difference in understanding the importance of smoking on arthritis between current smokers (VAS mean; SD 7.06; 2.35) and never smokers (VAS mean; SD 7.37; 2.15) (p=0.115) and between current smokers and ex-smokers (Mean; SD 7.74; 1.87) (p=0.23). 73% (16/22) of current smokers motivation to give up smoking score increased after they were given information on adverse effects of smoking on RA (mean VAS 4.43 before; 5.79 after) (p=0.03). 27% (6/22) did not change, none decreased. 50% (11/22) of patients felt lack of support and help prevented them stopping smoking. Preferred methods for smoking cessation help were: leaflets 41%; verbal advice 9%; GP review 18%. 54% (22/41) of ex-smokers were happy to speak to the current smokers to provide tips on stopping smoking. Conclusions: This small study suggests that brief educational intervention may help motivate patients to give up smoking. Lack of support is a common difficulty patients perceive when they try to give up smoking. As RA outcomes are worsened by smoking, clinicians need to be more proactive about promoting smoking cessation. Outpatient appointments provide a good opportunity for this. Disclosure of Interest: None declared